Unemployment as a Consequence of the Liquidation of State Agricultural Farms in 1991-2003 - Małgorzata Machałek (Studia Historiae Oeconomicae)
State Agricultural Farms (SAF) were liquidated on the basis of an act adopted in 1991. During the work on the act, the focus was exclusively on issues related to ownership and economic transformations, while the social consequences were not taken into account. SAF employees, especially agricultural workers, constituted a specific, historically shaped socio-professional group characterized by relatively low education and narrow professional qualifications. The aim of article is to identify the genesis of social problems in post-statehood areas, especially unemployment and its regional variation. The source base of the study is mainly the Reports of the Agricultural Property Agency of the State Treasury and sociological research reports carried out in post-statehood areas. The main finding of the research is that policy decisions to abolish state farms were made without taking into account their specific characteristics and territorial distribution. Their mentality was shaped by the nature of work and everyday life, which was entirely connected with the workplace. The workplace organized most of the living and social matters for employees and their families. After the liquidation of the State Agricultural Farms, employees were unable to find their place on the –labour market. Large-area farms established on the basis of the former SAFs radically limited employment, and the lack of appropriate skills and limited demand for labour outside agriculture worsened the situation of blue collar workers in particular. Regional differences were of particular importance for the scale of unemployment – where SAFs dominated, the unemployment problem persists even three decades after their liquidation, although it no longer concerns only former SAF employees, but all residents of former SAF areas.